Environmental enrichment techniques and tryptophan supplementation used to improve the quality of life and animal welfare of Nile tilapia - Favero Neto, João [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (Elsevier, 2020)
The adoption of high standards of animal welfare improves the quality of life for animals being reared and produces improved end products for consumers. In this study, we investigate the role of environmental enrichment and tryptophan supplementation in increasing animal welfare indices in tilapia. To do this, the environment where fish are reared is enriched using artificial aquatic plants and shelters, and their diet is supplemented with tryptophan. Animal welfare parameters are estimated and compared to verify this enrichment. The use of environmental enrichment and tryptophan supplements significantly influences the parameters of animal welfare in Nile tilapia, indicating their preference for enriched environments by reducing stereotypical and aggressive behavior. We emphasize the contribution that this study has in applying the concept of animal welfare in fish production, given that the simple and low cost enrichments used had a positive impact on the quality of life of the animals.
Keywords: Aggressive behavior; Animal behavior; Oreochromis niloticus; Preference; Stereotypes